Konstruksi Body Positivity Dalam Akun @Yitty - Putri Raissa Zaravina (Jurnal Ilmu Komunikasi, 2022)
The hegemony of body idealization has shackled women with non-ideal bodies for far too long. The body positivity movement emerged as a resistance to this hegemony. Representations of women with non-ideal bodies began to gain visibility on social media along with attention the body positivity movement received. This attracts the attention of brands and influencers to participate in integrating body positivity values in their products and marketing. One of the brands that promotes body positivity is YITTY. YITTY is a shapewear line founded by Lizzo, an American musician, in 2022. Uniquely, YITTY carries a mission of inclusivity to accommodate various body shapes with its products. YITTY's vision is also shown in marketing their products on social media. Due to the interesting facts about YITTY, researchers investigated the phenomenon of commodification of body positivity by brands with a focus on YITTY. This research will highlight how the construction of body positivity is produced on the @YITTY Instagram account. This research is a descriptive quantitative research. To find answers to research questions, Thwaites textual analysis was used. Textual analysis does not aim to find absolute meaning, because meaning is multi-interpretative. The results of this study show that (1) the body positivity produced on the @YITTY account supports the narrative that women with imperfect bodies can still appear confident and enjoy a glamorous life; and (2) There are still traces of capitalization of women's bodies in the form of objectification by showing only certain parts of the body.